Supply Chain Management A Logistics Perspective - Langley, C. John; Novack, Robert A.; Gibson, Brian J.; Coyle, John J. (Cengage, 2025)
Using a reader-friendly and straightforward approach, Supply chain management a logistics perspective, 12th Edition, blends logistics theory with practical applications. The latest content highlights emerging issues, technology developments and global changes in the constantly evolving and critically-important field of supply chain management. This edition examines today's real companies and how public and private organizations are responding to the continuing pressure to modernize and transform their supply chains. Dive into real-world businesses and see how organizations respond to the ongoing need for modernization in their supply chains. Experience hands-on learning with updated features, brief cases and global content -- providing a glimpse into the decisions supply chain managers make daily. Each chapter begins with profiles that spotlight real organizations, people or events -- underlining the significance of current supply chain matters.